(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The efficiency of innovative methods in teaching foreign languages is a topic of interest in educational research. Various scientific studies have explored the effectiveness of different approaches, technologies, and pedagogical strategies